Traumatic stress in caregivers of adult patients with cancer: A scoping review - Elizaveta Klekovkina; Maya A. Stern; Carmine Malfitano; Esme Fuller-Thomson (Archives of Gerontology and Geriatrics Plus)
Objective: The goal of this review was to critically review the research literature on traumatic stress in caregivers of adult cancer patients. Objectives included identifying the prevalence of significant traumatic stress symptoms, themes within the literature, and factors that are associated with traumatic stress in this population. Methods: A search was conducted of APA PsycInfo, MEDLINE, Embase, and CINAHL. Two authors screened abstracts and full-texts and extracted data from included articles. A total of 1,150 unique titles and abstracts were identified, with 2f articles selected for full-text screening after title and abstract screening. There were 23 studies which were included in the review. Results: Most studies reported a prevalence of PTSD of 15 % and above. The caregivers of newly diagnosed patients, those with recurrent cancer, and those on active treatment were the most distressed. Caregivers of patients who had completed treatment and those of longer-term survivors were less distressed. Significant associations were identified between caregiver traumatic stress and caregiver and patient psychological comorbidity, lower social support, higher caregiver burden, and patient's greater physical symptoms. Conclusion: This scoping review reveals that a substantial proportion of caregivers of adult patients with cancer experience traumatic stress. However, the majority of published studies are cross-sectional, with small sample sizes, and a lack of racial and gender diversity. There is an urgent need for further research, including on proactive and tailored interventions provided at the time of diagnosis or recurrence of the disease.